Wild shore : exploring Lake Superior by kayak - Breining, Greg (University of Minnesota Press, 2000)
Over two years, sportsman, writer, and world traveler Greg Breining set out to circle Lake Superior by kayak, a means of travel that allowed him to visit the lakes places of rare beauty and solitude, experience its wildly varied moods, and see its remote historic sites and isolated communities. Wild Shore is a tale of outdoor adventure, odd characters, humorous stories, and quiet reflection.